Folicullar bronchiolitis as phenotype associated with CD25 deficiency - Bezrodnik, Liliana (2014)
Regulatory T cells (CD4+CD25+FOXp3+) are subsets of T cells involved in the maintenance of peripheral self tolerance by actively suppressing the activation and expansion of autoreactive T cells.1 Signaling through the interleukin-2 receptor (IL-2R) contributes to T-cell tolerance by controlling three important aspects of Treg biology. CD25 is the α-chain of the IL-2R that, in concert with the β-chain and γ-chain, constitutes the complete IL-2R. 2 CD25 only contributes to IL-2 binding affinity but not to the recruitment of signaling molecules. However, its importance in the development of a normal immune response is emphasized by the finding that a truncation mutant of CD25 results in an immunodeficiency in humans characterized by an increased susceptibility to viral, bacterial and fungal infections. 3 In 1997, Sharfe et al. described an infant with severe bacterial, viral, and fungal infections. Counts of autologous T lymphocytes were moderately low, T cells displayed a weak proliferative response to mitogens in vitro, and the patient displayed no rejection of an allogeneic skin graft. However, unlike children with SCID, the patient besides not having circulating T cells, also developed peripheral lymphocytic proliferation and autoimmune primary biliary cirrhosis. 4 We present the first female argentine patient with mutation in CD25 associated with chronic and severe inflammatory lung disease (Follicular bronchiolitis with lymphocyte hyperplasia), eczema and infections. She has no expression of CD25 on CD4+ T cells and extremely low amount of Tregs.